Supplementation of Micronutrients against COVID-19 - Unnithan, Ajaya Kumar Ayyappan (Archives of Clinical and Biomedical Research, 2022)
Background and objectives: There is no pharmacological treatment with proven efficacy against coronavirus disease-19 (COVID-19). Certain micronutrients have roles in the maintenance of an effective immune system. From the point of view of public health, it will be good to adopt a nutritional strategy to enhance the immunity of the general population against viral diseases. Method and study design: A review was done to know the evidence for the antiviral and immune- modulatory properties of micronutrients. A search was done in PubMed, Scopus, and Google Scholar for the nutrients with proven effect against viral infection. Experimental studies, clinical studies, reviews, and meta-analyses were studied descriptively. Results: There are experimental studies about the effects of micronutrients against viral infection. Vitamins such as A, B6, B12, C, D, E, and folate, and trace elements such as zinc, selenium, iron, magnesium, and copper boost the immune response. The antioxidants like vitamin C and vitamin E can help in controlling the ‘cytokine storm’, produced by excessive inflammation. Vitamin D can increase anti- inflammatory cytokines. Selenium and zinc can protect the lungs in acute respiratory distress syndrome. There are many meta-analyses on the randomized controlled trials (RCT) about the effect of micronutrients on viral infection. The analyses of the trials supplementing vitamin C, vitamin D, vitamin E, and selenium have shown significance. Conclusions: There is level 2A evidence for the beneficial effects of vitamins and micronutrients in modulating the immunity against viral infections. So a program for nutritional supplementation of these can help in fighting the pandemic. Micronutrients with anti-inflammatory and antioxidant properties can reduce the severity of ‘cytokine storm’.